2017
DOI: 10.5751/es-09705-220421
|View full text |Cite
|
Sign up to set email alerts
|

Ways forward for resilience thinking: lessons from the field for those exploring social-ecological systems in agriculture and natural resource management

Abstract: . 2017. Ways forward for resilience thinking: lessons from the field for those exploring social-ecological systems in agriculture and natural resource management. Ecology and Society 22 (4) ABSTRACT. Resilience thinking appears to offer a holistic approach that can be used by social researchers to interpret past and contemporary conditions and identify possible futures for social-ecological systems (SES). Resilience thinking is shaping contemporary environmental policy and its implementation in Australia, Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Without weighing variables, certain factors such as soil fertility, slope or access to public services would be considered on an equal level as criteria related to community agency or agrarian structure. The proposed methodology includes aspects that are normally invisible, revealing power relations and transformation processes that alter structures and predominant social dynamics within communities (21,85).…”
Section: Results Discussion Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without weighing variables, certain factors such as soil fertility, slope or access to public services would be considered on an equal level as criteria related to community agency or agrarian structure. The proposed methodology includes aspects that are normally invisible, revealing power relations and transformation processes that alter structures and predominant social dynamics within communities (21,85).…”
Section: Results Discussion Conclusionmentioning
confidence: 99%
“…From the point of view of the elite, resilience is understood to be adaptation to conditions of inequality and injustice, which agrees well with neoliberal (20) and Keynesian discourse, in other words, maintaining the status quo . On the other hand, those with less power understand resilience to be transformation conducive of conditions ofjustice, which can lead to the destruction of the predominant social system (1,2124).…”
Section: Introductionmentioning
confidence: 99%
“…Sinclair et al [51] reported that the role of human agency is critical to understanding system resilience, which is the capacity of individuals to make sense of change. The results revealed that the indicators of the use of organic fertilizers and pesticides, the soil fertility index, water use efficiency (g/m 3 ), trust in government, access to advisory services (extension), on-the-job training, and diversity of marketing are at the manageable (moderate) level.…”
Section: Discussionmentioning
confidence: 99%
“…Without weighing variables, certain factors such as soil fertility, slope or access to public services would be considered on an equal level as criteria related to community agency or agrarian structure. The proposed methodology includes aspects that are normally invisible, revealing power relations and transformation processes that alter structures and predominant social dynamics within communities [21,103]. Fig 4 shows the results of calculating resilience without considering AS or agency, utilizing criteria associated with productive practices and biophysical conditions in comparison with the weighted average using all the proposed variables.…”
Section: Plos Onementioning
confidence: 99%